The Developmment of Learning Model of Basic Technique in the College Students of PJKR - Ari Kurnia; Dian Estu Prasetyo; Zuhar Ricky (The Future of Education Journal, 2022)
The model development uses the ADDIE model which consists of 5 stages, namely, analysis (analyze), design (design), development (development), implementation (implementation), evaluation (evaluation). The five stages were carried out through analysis of student needs, and analysis of student characteristics. Then the validation test was carried out by 4 validators (expert team), practicality test by PJOK lecturers and 10 students, after the model was categorized as valid and practical, then the effectiveness test was carried out. The results of the research on developing learning models of basic badminton techniques for physical education students, the validity test obtained percentage data with an average of 92.85% categorized as very valid, the practicality test by PJOK lecturers with a percentage of 75% was categorized as valid, and the student practicality test with a percentage of 92.5% was categorized as very practical, while the effectiveness test with a percentage of 80% was categorized as very effective. Based on the results obtained, the basic badminton technique learning model in PJOK learning is categorized as valid, practical, and effective.